2004
DOI: 10.1038/sj.onc.1208228
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of Wilms tumors reveals connections to kidney morphogenesis and expression patterns associated with anaplasia

Abstract: Anaplasia (unfavorable histology) is associated with therapy resistance and poor prognosis of Wilms tumor, but the molecular basis for this phenotype is unclear. Here, we used a cDNA array with 9240 clones relevant to cancer biology and/or kidney development to examine the expression profiles of 54 Wilms tumors, five normal kidneys and fetal kidney. By linking genes differentially expressed between fetal kidney and Wilms tumors to kidney morphogenesis, we found that genes expressed at a higher level in Wilms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 74 publications
3
35
0
2
Order By: Relevance
“…Therefore, we suggest that CRABP-II may differentially regulate the function of MycN, leading to the increased cell migration phenotype observed in tumors overexpressing CRABP-II. Other reports have also shown that in Wilms tumors, very high levels of CRABP-II correlate with poor clinical outcome (46), and a decrease in cell invasion occurs after CRABP-II inhibition in head and neck sarcoma (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we suggest that CRABP-II may differentially regulate the function of MycN, leading to the increased cell migration phenotype observed in tumors overexpressing CRABP-II. Other reports have also shown that in Wilms tumors, very high levels of CRABP-II correlate with poor clinical outcome (46), and a decrease in cell invasion occurs after CRABP-II inhibition in head and neck sarcoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…From analysis of the published microarray data, we found that CRABP-II was expressed in these cell lines, irrespective of the estrogen status but that all of these cell lines expressed high c-myc levels. A previous study from our lab identified both MycN and CRABP-II overexpression in Wilms tumors (46), and expression of MycN correlates with CRABP-II levels in these tumors. 3 Moreover, CRABP-II overexpression in tumors is not explained by their sensitivity or resistance to RA.…”
Section: Discussionmentioning
confidence: 99%
“…In total, genomic abnormalities were found in 29/38 tumors using this approach. Eight tumors with segmental 16q loss of heterozygosity due to deletion were detected (patients 4,7,13,14,20,21,26, and 27 in Table 1). In addition, one tumor (patient 28) exhibited copy-number neutral imbalance of the entire chromosome 16.…”
Section: Q Deletions Are Confined To Immature Tumor Tissue Elementsmentioning
confidence: 99%
“…Gene expression studies have provided additional evidence for the hypothesis that Wilms tumor results from a differentiation block in embryonic kidney formation; genes overexpressed in Wilms tumor are also expressed at the time of the first contact between the ureteric bud and the metanephric mesenchyme, while genes underrepresented in WTs are typically expressed later in kidney development. 3,4 The origin of WTs from potential renal precursors is also supported by the association of Wilms tumor with persistent patches of embryonic tissue in adjacent normal kidney tissue, known as nephrogenic rests. 5 Considering the similarities between Wilms tumor and the developing kidney, it is not surprising that several of the genes affected by somatic mutations in WTs are involved in embryonic kidney development and have been implicated in syndromes of genito-urinary malformation.…”
mentioning
confidence: 97%
“…Failure in FGF/EGF feedback control by genes such as Sprouty might contribute to the undifferentiated metanephric blastema found in Wilms' tumor, where the advanced stage of the disease is known to be correlated with persistent expression of early blastemal markers such as Cited1 and Meox1 (Williams et al, 2004;Li et al, 2005;Lovvorn et al, 2007a;Lovvorn et al, 2007b). The FGF/EGF signaling pathway components that are disrupted by Spry1, or genes that alter Spry1 activity, might represent novel therapeutic targets to combat Wilms' tumor and other cancers that arise from parent stem cells that normally display a requirement for FGF signaling during self-renewal.…”
Section: Research Articlementioning
confidence: 99%